Ξαναδιαβάζοντας την υλική αρχαιότητα στην ποίηση του Κ. Π. Καβάφη: Με αφορμή μια πρόσφατη μελέτη - Γκάρτζιου-Tάττη, Αριάδνη (Σύγκριση/Comparaison/Comparison, 2025)
Rereading material antiquity in C. P. Cavafy's poetry: On the occasion of a recent monograph Inspired by Takis Kayalis’ recent monograph (Cavafy's Hellenistic Antiquities. History, Archaeology, Empire, Palgrave Macmillan 2024), this paper attempts to highlight the perpetual dialogue between C. P. Cavafy's poetics and his peculiar use of material evidence concerning the literary, political, artistic and erotic receptions of antiquity at the turn of the 20th century. A brief overview of the primary evidence on Orophernes and Caesarion that is accessible to 21st-century historians shedslight not only on C. P. Cavafy’s poetic uses of specific material remnants of Greco-Roman antiquity but also on Kayalis’ interpretations of Cavafy’s numismatic rendering of the figure of Orophernes, of the poet’s readings of the fictional inscriptions of Caesarion and Lefkios and of the debates on homoeroticism and culture taking place in the context of the British Empire. This presentation of ancient sources and recent findings, from the viewpoint of a scholar of the Hellenistic era, provides new grounds for critical framings of the complex bonds between antiquity and modern literature.